Science and literature: Are the knowledge wars finally over? - Roslynn Haynes (Mètode Science Studies Journal: Annual Review)
Since alchemy first challenged the authority of the Church, the relative status of specialized, scientific knowledge and high culture has been hotly contested. For centuries writers, as champions of culture, have retaliated against the claims of science by satirising its practitioners as being either evil, obsessive and possibly mad, or foolish and inept inventors whose experiments continually misfire. Examples of both these groups are discussed in their historical context. Around the end of the twentieth century a new genre designated «lab-lit» appeared. In this scientists are portrayed not as stereotypes but as ordinary people, pursuing science as they might any other profession within a life context and engaged with the ethical and sociological problems it involves. Reasons for the emergence of lab-lit are considered.